Forensic investigation of the cause(s) of slippery ultra-thin bonded wearing course of an asphalt pavement: influence of binder content. Issue Volume 19:Issued 7(2018) (3rd July 2018) - Muñoz, J. F.; Balachandran, C.; Yao, Y.; Shastry, A.; Perry, L.; Beyene, M. A.; Arnold, T.
Abstract: This paper documents the second part of a forensic investigation performed to determine the causes of loss of skid resistance and bleeding in two pavement sections rehabilitated with an ultra-thin bonded wearing course. The first part of the study explored the influence of the aggregate fraction on the loss of skid resistance. This second part focuses on binder-related issues to understand the cause of the bleeding. A detailed investigation was performed on cores removed from both sections to quantify the binder content profile with depth. The chemical characteristics of all the recovered binders were determined using Fourier transform infrared spectroscopy and X-ray fluorescence spectroscopy. The results suggested that bleeding due to excess binder in the tack coat contributed to this deleterious performance. Chemical analysis identified an upward migration of a part of the binder from the interface and confirmed this hypothesis.